2019
DOI: 10.1016/j.jsbmb.2018.08.006
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of a novel analog of calcitriol and its biological evaluation as antitumor agent

Abstract: Calcitriol analogs have shown promising potential as compounds to be used in cancer chemotherapy. This report presents the synthesis of a novel vitamin D derivative with an amide and a carboxyl group in its side chain, called ML-344. In addition, we report its in vitro antitumor activity and its in vivo calcemic effects. We demonstrate that the analog decreases cell viability and retards cell migration of different breast, glioblastoma and head and neck cancer cell lines. Additionally, unlike calcitriol, ML-34… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 33 publications
0
7
0
Order By: Relevance
“…A number of findings indicate that 1,25‐dihydroxyvitamin D 3 can stimulate differentiation and suppress proliferation in several cell types . In addition to the suppression of proliferation, 1,25‐dihydroxyvitamin D 3 can also affect viability . The effects may vary in different cells and under different conditions.…”
Section: Vitamin D and Inhibition Of Cellular Proliferation: A Role Imentioning
confidence: 99%
See 2 more Smart Citations
“…A number of findings indicate that 1,25‐dihydroxyvitamin D 3 can stimulate differentiation and suppress proliferation in several cell types . In addition to the suppression of proliferation, 1,25‐dihydroxyvitamin D 3 can also affect viability . The effects may vary in different cells and under different conditions.…”
Section: Vitamin D and Inhibition Of Cellular Proliferation: A Role Imentioning
confidence: 99%
“…Vitamin D analogues have been shown to inhibit both cellular growth and viability in various types of cancer cells . So far, relatively few studies have been conducted on tumours of the nervous system . Most of these studies have been performed on different types of glioma cells.…”
Section: Vitamin D and Inhibition Of Cellular Proliferation: A Role Imentioning
confidence: 99%
See 1 more Smart Citation
“…Ferronato et al (16) examined the effect of a synthetic novel derivative of vitamin D3 called ML-344 on in vitro antitumor activity and in vivo calcemic effects. They also had the computational studies to examine its affinity for VDR through in silico assays.…”
Section: Results Of In Vivo Studiesmentioning
confidence: 99%
“…Beyond the calcium balance role of vitamin D and the beneficial effects on bone, due to the existence of vitamin D receptor (VDR) throughout body especially in the brain, vitamin D regulates the various types of function such as cell proliferation and differentiation, apoptosis, angiogenesis, cell invasion, DNA repair, metabolism, and inflammation (12)(13)(14). Although antitumor efficacy of vitamin D3 is observed in supraphysiological doses, which in turn may cause hypercalcemia, recent in vivo studies have shown that its analogs have beneficial effects on glioma cells without calcemic effect (15)(16)(17)(18). Here, we review studies about the effect of vitamin D3 and its analogs on gliomas with special emphasis on GBM.…”
mentioning
confidence: 99%